Иван Петрович Кулибин, Иван Иванович Ползунов, Ефим Алексеевич и Мирон Ефимович Черепановы - Минаева Ольга Дмитриевна (Великие умы России, 2016)
Экземпляры: ф.8 (20220505) / Инвентарный номер: 62142 / Цена: / Сис.шифр: 72.3(2) / Авт.знак: М 61 / ББК: 72.3д(2)